Botulism in the Brazilian Amazon: a life-threatening disease in a neglected population - Louise Makarem Oliveira; Daniel Buzaglo Gonçalves; Lucas de Cristo Rojas Cabral; Marília Rosa Abtibol Bernardino; Pablo Vinícius Silveira Feitoza (Arquivos de Neuro-Psiquiatria)
Background Botulism is a rare and potentially fatal neuroparalytic syndrome caused by the gram-positive anaerobe spore-forming bacterium Clostridium botulinum. The microorganism produces a neurotoxin that inhibits the presynaptic release of acetylcholine at the neuromuscular junction, clinically leading to a myasthenic syndrome. Objective To describe the recent outbreak of botulism cases and its demographic, clinical, and laboratory characteristics. Methods We report 4 patients with botulism in the recent outbreak occurred between 2017 and 2019 in the state of Amazon. Results Out of four patients with botulism, three contracted it from eating contaminated food and one had wound botulism. We emphasize the excellent clinical outcome of the different disease presentations in our case series. Conclusion The temporal proximity of these reports may suggest a new rise in the number of cases in the upcoming years. A possible hypothesis is that the rarity of the disease decreased the awareness regarding the primary prevention or even a diagnosis by an untrained physician.